The Cell Line Ontology and its use in tagging cell line names in biomedical text - Sarntivijai, Sirarat; Ade, Alexander S; Athey, Brian D; States, David J (AMIA ... Annual Symposium proceedings, 2007)
Cell lines are used extensively throughout biomedical research, but the nomenclature describing cell lines has not been standardized; many ambiguous names appear in the published literature. The Cell Line Ontology is a well-structured collection of names for cell lines cultured in vitro. This ontology collates names from ATCC, HyperCLDB and MeSH in an informative format and specifies relationships between cell lines including derivation and homolog. Tagging cell line names in text requires an integrated approach.